Driving Clicks towards Ecommerce Website: The Effect of Beauty Product Review Article Content Quality on Ecommerce Blog - Adhiguna, Hizky Mahar; Aruan, Daniel Tumpal Hamonangan (International Journal of Business Studies, 2023)
Ecommerce blogs are increasingly popular for providing product information, reviews and driving traffic to ecommerce websites. Recent study reported 76% of ecommerce users trust online reviews as much as recommendations from family or friends. This indicates that the content found in product reviews blog plays a crucial role in driving users to ecommerce websites. This study examines the impact of content quality in beauty product review articles on click intention towards ecommerce websites. Content quality is evaluated based on Substance, Writing and Language, Presentation of Content, References, Authorship, Audience, and Advertisements. Semi-experimental and logistic regression analyses were conducted on survey data from 225 female respondents who evaluated 126 beauty product review articles. Findings indicate a positive association between Substance, Presentation of Content, and Authorship with Click Intention, while Writing and Language, References, and Advertisement show no significant correlation. Furthermore, a negative relationship exists between Audience and Click Intention. This research addresses the literature gap by identifying significant factors of content quality that influence click intention, emphasizing the importance of content quality assessment and providing strategies for improvement. The study offers valuable insights for ecommerce companies to optimize marketing expenses and achieve key performance indicators.